2023
DOI: 10.1111/pce.14672
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gene regulatory networks improving spike fertility through regulation of floret primordia fate in wheat

Abstract: The developmental process of spike is critical for spike fertility through affecting floret primordia fate in wheat; however, the genetic regulation of this dynamic and complex developmental process remains unclear. Here, we conducted a high temporal‐resolution analysis of spike transcriptomes and monitored the number and morphology of floret primordia within spike. The development of all floret primordia in a spike was clearly separated into three distinct phases: differentiation, pre‐dimorphism and dimorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The morphological development of FP before polarization was a significant factor in restricting the increase of NFFs. Ugarte et al (2010) showed that a low red/far-red ratio accelerated floret development and was associated with a lower number of living florets; on the contrary, Zhang et al (2023) found that accelerating morphological development of FP by increasing plant space improved the number of fertile florets in wheat. One possible reason for the discrepancies between these studies was that a 'stress treatment' or 'optimization treatment' was applied to the plants, which affected the plant's adjustment and use of available resources.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological development of FP before polarization was a significant factor in restricting the increase of NFFs. Ugarte et al (2010) showed that a low red/far-red ratio accelerated floret development and was associated with a lower number of living florets; on the contrary, Zhang et al (2023) found that accelerating morphological development of FP by increasing plant space improved the number of fertile florets in wheat. One possible reason for the discrepancies between these studies was that a 'stress treatment' or 'optimization treatment' was applied to the plants, which affected the plant's adjustment and use of available resources.…”
Section: Discussionmentioning
confidence: 99%